Reduced serum neurotrophic factors and monoamine neurotransmitters in epilepsy patients with comorbid depression - Sun, Shulei; Han, Yuxiang; Liu, Xiaoyun; Yang, Liling; Han, Tao; Lin, Youting; Feng, Yabo (Frontiers in Neurology, 2024)
Objective This study aimed to investigate the roles of neurotrophic factors (NTFs), monoamine neurotransmitters, and inflammatory processes in the pathophysiology of the comorbidity of epilepsy and depression. Methods A retrospective analysis was conducted with 57 epilepsy patients (PWE), 50 patients with epilepsy and comorbid depression (PWECD), and 47 healthy controls (HC) admitted between June 2020 and June 2024. Serum levels of brain-derived neurotrophic factor (BDNF), glial-derived neurotrophic factor (GDNF), 5-hydroxytryptamine (5-HT), norepinephrine (NE), dopamine (DA), interleukin-1β (IL-1β), and interleukin-6 (IL-6) were measured using enzyme-linked immunosorbent assay (ELISA). Additionally, BDNF and GDNF levels in cerebrospinal fluid (CSF) samples were analyzed from selected patients in the PWE and PWECD groups. Results Serum BDNF levels were significantly lower in both PWE and PWECD groups compared to HC, while no differences between the former two groups. GDNF levels were lower in PWECD compared to HC, but not between PWE and HC. Serum 5-HT was significantly reduced in PWECD compared to both HC and PWE groups. No significant differences were observed in serum DA, NE, and IL-6 levels across the groups. Serum IL-1β levels were elevated in the PWECD group compared to the HC group. The Self-Rating Depression Scale (SDS) score negatively correlated with serum 5-HT and GDNF levels. In terms of predictive ability, serum BDNF demonstrated higher accuracy for the diagnosis of epilepsy [area under the curve, AUC = 0.701, 95% confidence intervals (95% CI) 0.601 ~ 0.801], while serum 5-HT was the best marker for predicting the development of depression in epilepsy patients (AUC = 0.727, 95% CI 0.632 ~ 0.821). No significant correlation was found between serum and CSF BDNF levels within the same subject (r = 0.155; p = 0.221; Spearman correlation), and CSF GDNF levels were too low to be clinically informative. Conclusion The findings suggest the involvement of NTFs, monoamine neurotransmitters, and inflammatory processes in the pathogenesis of epilepsy and depression. Decreased serum BDNF levels correlate with epilepsy but not necessarily with comorbid depression, while serum GDNF and 5-HT show potential clinical value in diagnosing this comorbidity. However, the deficient levels of NTFs in CSF suggest a need for more sensitive detection methods.